2006
DOI: 10.1111/j.1365-2265.2006.02505.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of abdominal obesity on insulin sensitivity and serum lipid and cytokine concentrations in African women

Abstract: Although previous studies have shown that African subjects have a lower visceral adipose depot size than European subjects, abdominal obesity is still associated with insulin resistance and dyslipidaemia. The association between abdominal obesity and metabolic dysfunction within this population is not dependent upon IL-6, IL-8 or IL-18.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 55 publications
(82 reference statements)
4
30
0
Order By: Relevance
“…The latter hypothesis is unlikely since it has been shown that waist circumference, independently of BMI, is a determinant of insulin sensitivity in this population group. 80 It is also possible that subcutaneous abdominal fat may play a more prominent role in determining whole-body insulin sensitivity in African than European females, as has been observed in a previous study. 79 Previous investigators have suggested that obesity in African subjects is benign.…”
Section: Obesity and Cardiovascular Disease In Africamentioning
confidence: 49%
“…The latter hypothesis is unlikely since it has been shown that waist circumference, independently of BMI, is a determinant of insulin sensitivity in this population group. 80 It is also possible that subcutaneous abdominal fat may play a more prominent role in determining whole-body insulin sensitivity in African than European females, as has been observed in a previous study. 79 Previous investigators have suggested that obesity in African subjects is benign.…”
Section: Obesity and Cardiovascular Disease In Africamentioning
confidence: 49%
“…Similarly, Hung et al (19) showed an association between the serum IL-18 levels and the metabolic syndrome in a representative sample of 910 subjects aged 27-77 years (19). Other studies examining individual risk factors for CVD have also found associations between increasing circulating IL-18 levels and individual CVD risk factors such as central adiposity (43,44), hyperglycemia (45), and insulin resistance (43,46).…”
Section: Discussionmentioning
confidence: 89%
“…Abdominal obesity could contribute to this association. Several studies reported an inverse association between waist-to-hip ratio and plasma HDL cholesterol (34,35). Additional adjustment for waist-to-hip ratio attenuated the associations between television viewing and low HDL cholesterol, but it remained significant (P ϭ 0.04).…”
Section: -Television Viewing and Relative Likelihood (Ors And 95% Ci)mentioning
confidence: 97%